(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The main purpose of the article – to consider the features of the image Olzhas Suleimenov in lyrical autobiographical lyric poem «The Balcony» and his interpretation of the story of the same movie makers. The author analyzes the compositional and structural features of the Suleimenov’s poem, built as a retro remembrance of lyrical hero, a story in the first person about the events happened twenty-five years ago, which took place in the center of Almaty. «Balcony» is perceived by researchers as a small lyrical genre, the lyrical sketch. From the point of view of the author, the poem clearly visible traces of elegy and philosophical genre tolgau, whose roots go back in Kazakh folklore. This idea is the starting point in the analysis of ground plots Olzhas Suleimenov poems and film Kalykbek Salykova. The article discusses problems of implementation of the plot of the poem, the basic gait of heroes, motives of a film that transmit the spirit of generations of the 60s of the twentieth century.